The adder (Vipera berus) in Southern Altay Mountains: population characteristics, distribution, morphology and phylogenetic position - Cui,Shaopeng; Luo,Xiao; Chen,Daiqiang; Sun,Jizhou; Chu,Hongjun; Li,Chunwang; Jiang,Zhigang (PeerJ, 2016)
As the most widely distributed snake in Eurasia, the adder (Vipera berus) has been extensively investigated in Europe but poorly understood in Asia. The Southern Altay Mountains represent the adder’s southern distribution limit in Central Asia, whereas its population status has never been assessed. We conducted, for the first time, field surveys for the adder at two areas of Southern Altay Mountains using a combination of line transects and random searches. We also described the morphological characteristics of the collected specimens and conducted analyses of external morphology and molecular phylogeny. The results showed that the adder distributed in both survey sites and we recorded a total of 34 sightings. In Kanas river valley, the estimated encounter rate over a total of 137 km transects was 0.15 ± 0.05 sightings/km. The occurrence of melanism was only 17%. The small size was typical for the adders in Southern Altay Mountains in contrast to other geographic populations of the nominate subspecies. A phylogenetic tree obtained by Bayesian Inference based on DNA sequences of the mitochondrial cytochrome b (1,023 bp) grouped them within the Northern clade of the species but failed to separate them from the subspecies V. b. sachalinensis. Our discovery extends the distribution range of V. berus and provides a basis for further researches. We discuss the hypothesis that the adder expands its distribution border to the southwest along the mountains’ elevation gradient, but the population abundance declines gradually due to a drying climate.
Keywords: Vipera berus; Snake; Southern Altay Mountains; Species’ border; Population survey; Morphology; Geographical variation; Phylogenetic position